Evaluasi Fasilitas Olahraga pada Lapangan Alit Saputra di Kota Tabanan - Divayana, I Putu Ari; Semarajaya, Cokorda Gede Alit; Mayun, Ida Ayu (Jurnal Arsitektur Lansekap; Vol.8, No.1, April 2022DO - 10.24843/JAL.2022.v08.i01.p04, 2022)
Evaluation of sport facilities at Alit Saputra Field in Tabanan City . Alit Saputra Field has several sports facilities such as tennis courts, basketball courts and volleyball courts. However, for now the existence of these facilities is still somewhat inconvenient to use due to the presence of damaged facilities and a lack of standard equipment. Therefore, the evaluation of sports facilities has a very important role to maintain user comfort in the Alit Saputra Field. The aim of this study was to evaluate sports facilities by comparing them to exercise standards. The method used in this study was a survey and data collection was carried out through direct field observations, interviews, and questionnaires. Based on the research conducted, it was found that there are facilities and infrastructure that have been damaged and there is a lack of complete facilities for each of these sports facilities, so it is necessary to carry out repairs so that they can be used properly and comfortably by field users Alit Saputra. The suggestion in this research is that the manager must maintain the facilities in the field in order to keep functioning in comfortable conditions and along with the role of the user is expected to take part in maintaining all elements in the Alit Saputra Field.